Discussion of Helicobacter pylori infection issue in reports of the 19-th United European Gastroenterology Week - A. A. Sheptulin; Yu. V. Evsyutina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze reports of the 19-th United European Gastroenterology Week, devoted to diagnostics and treatment of Helicobacter pylori infection.Original positions. Prevalence of H. рylori continues to remain high all over the world. Now decrease of the standard triple mode of eradication of infection efficacy, related to growing clarithromycin resistance of H. рylori strains is observed. Overcoming of this resistance is promoted by new modes of eradication: sequential, «concomitant» triple therapy with levofloxacin. The choice of the specific mode depends on level of clarithromycin resistance in this region.Conclusion. Improvement of treatment efficacy can be achieved by development of new modes of eradication.